Organogenesis in Development - Koopman, Peter (Current topics in developmental biology, 2010)
Understanding organogenesis is central to current efforts to direct stem cell differentiation and function in the context of a complex organ. Defects in organogenesis are often the major manifestations of human genetic disease syndromes. This volume describes the development of 10 major organ systems, reviewed by experts in each, to provide an up-to-date overview for researchers within and outside the field, students, teachers and clinicians. Summarizes the key morphological and cellular events Emphasizes up-to-date research relating to molecula.